Calcium-based carbonate compound and hydrous composition

By employing a calcium-based carbonic acid compound with tailored viscosity in inorganic molded bodies, the challenges of fire resistance and carbon dioxide emissions are addressed, resulting in enhanced fire resistance and reduced environmental impact.

JP2025066249AActive Publication Date: 2025-04-23KONOSHIMA CHEMICAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023175700
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23
Estimated Expiration
2043-10-11

AI Technical Summary

Technical Problem

Existing inorganic molded bodies face challenges in achieving high fire resistance due to issues like surface shrinkage and back surface temperature rise during heating, and there is a need to reduce carbon dioxide emissions by reusing secondary carbon dioxide.

Method used

A calcium-based carbonic acid compound with specific viscosity ranges when dispersed in water is used, which suppresses the shrinkage of the heating surface and the rise in the back surface temperature, thereby enhancing the fire resistance of inorganic molded bodies. This compound is also produced using secondary carbon dioxide, reducing emissions.

Benefits of technology

The use of the calcium-based carbonic acid compound with controlled viscosity significantly improves the fire resistance of inorganic molded bodies by minimizing thermal conductivity and surface shrinkage, while also contributing to reduced carbon dioxide emissions through the reuse of secondary carbon dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066249000001_ABST
    Figure 2025066249000001_ABST
Patent Text Reader

Abstract

To provide a calcium-based carbonate compound and a hydrous composition capable of further reducing shrinkage of a heated surface and increase in a back surface temperature during heating when used in an inorganic molded body as a building material.SOLUTION: The calcium-based carbonate compound has a viscosity of 1000 cP or more and 2000 cP or less at 30 rpm in a state of being dispersed in water at a concentration of 33 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a calcium carbonate compound and a water-containing composition. [Background technology]

[0002] Inorganic molded bodies are molded bodies that are mostly composed of inorganic substances such as hydraulic materials and siliceous materials, and have properties such as fire resistance, light weight, high strength, and ease of workability, and therefore are widely used for exterior wall materials for houses, roof underlayment materials, eaves ceiling materials, and the like.

[0003] On the other hand, due to the recent increase in environmental awareness, attempts are being made to reuse by-products and by-produced energy, such as waste materials, exhaust gases, and waste heat, which are generated secondarily in industrial processes.

[0004] As a technology for promoting the reuse of waste while improving fire resistance, which is one of the important safety features required for inorganic molded bodies, a technology has been proposed in which seawater residue, which is mainly composed of calcium carbonate and magnesium hydroxide and is by-produced in the process of removing carbonates from seawater, is applied to a calcareous material (JP Patent Publication No. 2012-116685). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-116685 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, even with the above-mentioned techniques, shrinkage of the heated surface and an increase in the back surface temperature may occur when heated, and there is a demand for further improvement in the fire resistance of inorganic molded bodies as building materials.

[0007] Furthermore, carbon dioxide is becoming widely recognized as a greenhouse gas, and reuse and reduction of carbon dioxide emissions as a secondary product from industrial processes have become urgent issues.

[0008] An object of the present invention is to provide a calcium carbonate compound and a water-containing composition which are capable of exhibiting a higher level of fire resistance when used in an inorganic molded article as a building material. [Means for solving the problem]

[0009] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by the following configuration, and have completed the present invention.

[0010] In one embodiment, the present invention comprises: The present invention relates to a calcium carbonate compound having a viscosity of 1000 cP or more and 2000 cP or less at 30 rpm when dispersed in water at a concentration of 33% by mass.

[0011] According to the calcium carbonate compound, the viscosity of the dispersion liquid in which the calcium carbonate compound is dispersed at a predetermined concentration is within a specific range at 30 rpm, so that when the calcium carbonate compound is used in an inorganic molded body, the compound can exhibit a higher level of fire resistance. Although the reason for this is not clear, it is presumed as follows.

[0012] The inventors have conducted further investigations into the application of a dispersion of a calcium-based carbonate compound obtained in the manufacturing process of a synthetic calcium-based carbonate compound in its original state to the manufacturing process of an inorganic molded body, and have found that if the dispersion has the above-mentioned specific viscosity, it is possible to suppress the shrinkage of the heating surface and the increase in the back surface temperature during heating.

[0013] The dispersion liquid in which the calcium carbonate compound is dispersed has a relatively high viscosity within a specific range. This is presumably due to the fact that the aggregation of the calcium carbonate compound is reduced and the degree of dispersion in the form of primary particles is high. By directly incorporating the dispersion liquid containing the calcium carbonate compound in the form of primary particles during the production of the inorganic molded body, the calcium carbonate compound is uniformly dispersed in the form of primary particles in the inorganic molded body. As a result, the calcium carbonate compound functions as a so-called reinforcing material, thereby suppressing the shrinkage of the heating surface. In addition, the uniform dispersion of the low thermal conductive calcium carbonate compound enhances the insulation in the thickness direction of the inorganic molded body, thereby suppressing the rise in the back surface temperature.

[0014] It is believed that these combined effects make it possible to suppress to a higher degree the shrinkage of the heated surface and the increase in temperature of the back surface when heated, thereby enabling the inorganic molded body as a whole to exhibit a high level of fire resistance.

[0015] In this specification, the term "calcium-based carbonate compound" refers to a compound containing calcium carbonate as a main component, and is a concept that allows the inclusion or coexistence of other subcomponents that may be incorporated during the manufacturing process, etc. The calcium carbonate content in the calcium-based carbonate compound is preferably 80 mass% or more. The content ratio of calcium carbonate in the calcium-based carbonate compound can be suitably measured by XRF (X-ray fluorescence analysis).

[0016] In one embodiment, the viscosity of the dispersion liquid in which the calcium carbonate compound is dispersed in water at a concentration of 33% by mass is preferably 1000 cP to 2500 cP at 6 rpm, which improves the uniformity of the dispersion degree of the calcium carbonate compound and can suppress the shrinkage of the heating surface and the increase in the back surface temperature during heating to a higher level.

[0017] In one embodiment, the viscosity μ6 at 6 rpm of a dispersion liquid in which the calcium carbonate compound is dispersed in water at a concentration of 33% by mass is 30 rpm. 30Ratio μ6 / μ 30 is preferably 1.0 or more and 2.5 or less. This can reduce the thixotropy of the dispersion, and even if the stirring speed or shear force is high or low, the viscosity in both states does not deviate significantly and a certain degree of high viscosity is maintained. As a result, deformation and deterioration of the molded body when force is applied and released during molding, pressing, etc. in the inorganic molded body manufacturing process are suppressed, and an inorganic molded body having excellent fire resistance can be manufactured.

[0018] In one embodiment, the aspect ratio of the average major axis to the average minor axis of the calcium carbonate compound is preferably 2 or more and 19 or less. In one embodiment, the average particle size of the calcium carbonate compound as measured by a laser diffraction method is preferably 1.1 μm or more and 12.5 μm or less. In one embodiment, the average major axis of the calcium carbonate compound as measured by observation with a scanning electron microscope is preferably 0.5 μm or more and 25 μm or less. By satisfying one or a combination of these configurations, a specific range of viscosity can be suitably imparted to the dispersion liquid of the calcium carbonate compound.

[0019] In another embodiment, the present invention provides a method for producing a pharmaceutical composition comprising the steps of: The present invention relates to a water-containing composition containing water and the calcium carbonate compound.

[0020] Since the water-containing composition can have a viscosity in the specific range, the degree of the primary particle state of the calcium carbonate compound can be maintained at a high level. Therefore, when the water-containing composition is applied to the production of an inorganic molded body, the resulting inorganic molded body can be highly suppressed in shrinkage of the heating surface and increase in temperature of the back surface during heating.

[0021] In one embodiment, the water content of the water-containing composition may be 40% by mass or more and 99% by mass or less, whereby the water-containing composition can take the form of a so-called slurry.

[0022] In one embodiment, the water content of the water-containing composition may be 5% by mass or more and 60% by mass or less, whereby the water-containing composition can take the form of a so-called cake.

[0023] In one embodiment, the water-containing composition is preferably obtained without drying in the manufacturing process of the synthetic calcium carbonate compound. By using a synthetic calcium carbonate compound, which is a reaction product of calcium hydroxide and carbon dioxide gas (carbon dioxide), as the calcium carbonate compound, carbon dioxide generated secondarily in the industrial process can be reused, which contributes to reducing carbon dioxide emissions in the entire industrial process. Furthermore, since the water-containing composition is obtained without drying, it is possible to further reduce carbon dioxide emissions.

[0024] The present invention, in yet another embodiment, comprises The present invention relates to an inorganic formed body containing the calcium carbonate compound.

[0025] The inorganic molded body contains the calcium carbonate compound, and therefore can exhibit a higher level of fire resistance.

[0026] In yet another embodiment, the present invention comprises: The present invention also relates to a method for producing an inorganic molded product, which comprises a step of molding an inorganic composition containing the water-containing composition.

[0027] In this production method, the water-containing composition is subjected to the molding step as it is, so that an inorganic molded article having excellent fire resistance can be efficiently produced. [Brief description of the drawings]

[0028] [Figure 1] 1 is a SEM photograph of a calcium carbonate compound obtained from the water-containing composition of Example 1-1 of the present invention. [Diagram 2] 1 is a SEM photograph of a calcium carbonate compound obtained from the water-containing composition of Example 1-2 of the present invention. [Diagram 3]FIG. 2 is a partial perspective view showing a typical heating tester. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The calcium carbonate compound and water-containing composition according to one embodiment of the present invention will be described below. The present invention is not limited to these embodiments.

[0030] <Calcium carbonate compounds> The calcium carbonate compound according to the present embodiment is a calcium carbonate compound having a viscosity of 1000 cP or more and 2000 cP or less at 30 rpm when dispersed in water at a concentration of 33% by mass. The viscosity at 30 rpm is preferably 1100 cP or more and 1900 cP or less, and more preferably 1200 cP or more and 1800 cP or less. This provides good workability and allows the degree of primary particle state of the calcium carbonate compound to be maintained at a high level. When the dispersion is used to manufacture an inorganic molded body, it is possible to reduce the shrinkage of the heating surface and the increase in the back surface temperature during heating.

[0031] The viscosity at 6 rpm of the dispersion in which the calcium carbonate compound is dispersed in water at a concentration of 33% by mass is 1000 cP or more and 2500 cP or less. The viscosity at 6 rpm is preferably 1100 cP or more and 2400 cP or less, and more preferably 1200 cP or more and 2300 cP or less. This can improve the uniformity of the dispersion degree of the calcium carbonate compound. When the dispersion is used to manufacture an inorganic molded body, the shrinkage of the heating surface and the rise in the back surface temperature during heating can be suppressed to a higher level.

[0032] The viscosity μ at 6 rpm of the dispersion in which the calcium carbonate compound is dispersed in water at a concentration of 33% by mass is 30 Ratio μ6 / μ 30 The ratio μ6 / μ is 1.0 or more and 2.5 or less. 30is preferably 1.0 or more and 2.2 or less, and more preferably 1.0 or more and 1.8 or less, whereby the occurrence of thixotropy in the dispersion state can be suppressed, and deformation and deterioration of the molded body when a force is applied and released in the inorganic molded body production process can be prevented.

[0033] The crystal structure of the calcium carbonate compound may be a calcite type, an aragonite type, or a combination thereof. In order to provide the calcium carbonate compound with an aspect ratio as described below, it is preferable that the calcium carbonate compound contains at least an aragonite type crystal structure.

[0034] The aspect ratio of the average major axis to the average minor axis of the calcium carbonate compound is preferably 2 to 19, more preferably 2.5 to 17, and even more preferably 3 to 15. By setting the aspect ratio of the calcium carbonate compound within the above range, the dispersion of the calcium carbonate compound can preferably have a viscosity within the above range. In addition, the calcium carbonate compound with a high aspect ratio effectively functions as a reinforcing material, thereby suppressing shrinkage of the heating surface and an increase in the back surface temperature, and thereby allowing the inorganic molded body as a whole to exhibit excellent fire resistance.

[0035] When the inorganic molded body is produced by a papermaking method, the aspect ratio of the calcium carbonate compound is preferably 4 to 19, more preferably 6 to 18, and even more preferably 8 to 17. When the inorganic molded body is produced by an extrusion molding method, the aspect ratio of the calcium carbonate compound is preferably 2 to 12, more preferably 2.5 to 10, and even more preferably 3 to 8.

[0036] The average particle size of the calcium carbonate compound measured by a laser diffraction method is preferably 1.1 μm or more and 12.5 μm or less, more preferably 1.5 μm or more and 12 μm or less, and even more preferably 2 μm or more and 10 μm or less. This allows the dispersion of the calcium carbonate compound to have a suitable viscosity within the above range. In addition, the dispersibility of the calcium carbonate compound can be improved, and the shrinkage of the heating surface can be efficiently suppressed.

[0037] The average major axis of the calcium carbonate compound as observed by a scanning electron microscope is preferably 0.5 μm or more and 25 μm or less, more preferably 1 μm or more and 22 μm or less, and even more preferably 2 μm or more and 18 μm or less. This allows the dispersion of the calcium carbonate compound to have a suitable viscosity within the above range. In addition, the calcium carbonate compound is prevented from agglomerating with other components, and as a result, the shrinkage of the heating surface and the rise in the back surface temperature during heating can be prevented to a higher level.

[0038] The BET specific surface area of ​​the calcium carbonate compound is 1 m 2 / g or more 10m 2 / g or less, and 2 / g or more 9m 2 / g or less is more preferable, 2 / g or more 8m 2 This makes it possible to improve the dispersibility of the calcium carbonate compound, and as a result, it is possible to suppress the shrinkage of the heating surface and the rise in the back surface temperature during heating to a higher level.

[0039] In the X-ray diffraction measurement of the calcium carbonate compound, the peak intensity I a Calcite peak intensity I c Ratio to I a / I cis preferably 0.02 or more, more preferably 0.20 or more, and even more preferably 1.00 or more. This allows the calcium carbonate compound to be efficiently given a high aspect ratio, and the viscosity of the dispersion liquid to be appropriately controlled. In addition, the fire resistance of the inorganic molded body can be improved to a higher level.

[0040] The calcium carbonate compound is preferably a synthetic calcium carbonate compound. By using a synthetic calcium carbonate compound, which is a reaction product of calcium hydroxide and carbon dioxide gas (carbon dioxide), as the calcium carbonate compound, carbon dioxide secondarily generated in the industrial process can be reused, which contributes to reducing carbon dioxide emissions in the entire industrial process. In addition, in the process of producing magnesium hydroxide from seawater, the calcium carbonate compound by-produced in the process of removing carbonates in seawater and seawater residue mainly composed of magnesium hydroxide can be used as the calcium carbonate compound source.

[0041] <Water-containing composition> The water-containing composition according to the present embodiment contains water and the calcium carbonate compound. Since the water-containing composition contains the calcium carbonate compound having the above-mentioned structure, the water-containing composition can have a viscosity in the specific range.

[0042] The water content of the water-containing composition may be 40% by mass or more and 99% by mass or less, 50% by mass or more and 99% by mass or less, or 60% by mass or more and 99% by mass or less, whereby the water-containing composition can take the form of a so-called slurry.

[0043] The water content of the water-containing composition may be 5% by mass or more and 60% by mass or less, 10% by mass or more and 60% by mass or less, or 15% by mass or more and 60% by mass or less, whereby the water-containing composition can take the form of a so-called cake.

[0044] The method for measuring the water content of the water-containing composition is as described in the Examples.

[0045] The water-containing composition is preferably obtained without drying in the manufacturing process of the synthetic calcium carbonate compound (described later). By using a synthetic calcium carbonate compound, which is a reaction product of calcium hydroxide and carbon dioxide gas (carbon dioxide), as the calcium carbonate compound, carbon dioxide generated secondarily in the industrial process can be reused, which contributes to reducing carbon dioxide emissions in the entire industrial process. Furthermore, since the water-containing composition is obtained without drying, it is possible to further reduce carbon dioxide emissions.

[0046] The water-containing composition may contain, in addition to the calcium carbonate compound, any known optional components such as a surfactant, a viscosity modifier, other metals or metal salts, an acid, and an alkali.

[0047] <Method of producing calcium carbonate compound and method of producing water-containing composition> The method for synthesizing calcium carbonate compounds is not particularly limited, and known manufacturing methods can be used.Typically, the carbon dioxide gas method is preferred in which carbon dioxide gas is blown into milk of lime (a slurry in which excess slaked lime is added to a saturated aqueous solution of slaked lime) to carbonate it.The carbon dioxide gas used in the carbon dioxide gas method can be the flue gas of a lime calciner installed near a calcium carbonate compound manufacturing plant, or the exhaust gas from a boiler, a waste incinerator, or the like.

[0048] A known method can also be adopted as a method for imparting a predetermined aspect ratio to a calcium carbonate compound based on the carbon dioxide gas method.Specific examples of the method include a method for producing a calcium carbonate compound by adjusting the amount of carbon dioxide gas at each stage in the carbonation process, a method for producing a calcium carbonate compound by heating at the carbonation stage, a method for producing a calcium carbonate compound by using an acicular light calcium carbonate compound as a seed crystal in a slaked lime slurry, introducing carbon dioxide gas into the slurry, and growing the seed crystal to a desired particle size by a carbonation reaction, a method for producing a calcium carbonate compound by adding an aragonite-type acicular calcium carbonate compound to a slaked lime slurry and carrying out a carbonation reaction while stirring with a high stirring power, a method for producing an aragonite-type calcium carbonate compound by adding a phosphoric acid compound, a method for producing a calcium carbonate compound by adding a sulfate compound to obtain a spindle-shaped calcium carbonate compound, a method for producing an aragonite-type calcium carbonate compound by using a slaked lime slurry prepared with an alkaline aqueous solution, and a method for producing an aragonite-type calcium carbonate compound by using a slaked lime slurry prepared with water containing magnesium ions. By using one or a combination of two or more of these methods, a calcium carbonate compound having an aragonite-type crystal structure can be efficiently produced.

[0049] Among them, a preferred method for producing a calcium carbonate compound having a high aspect ratio and oil absorption is a method for producing a calcium carbonate compound in which needle-shaped synthetic calcium carbonate compound having an aragonite-type crystal structure is used as seed crystals in a slaked lime slurry, carbon dioxide gas is introduced into the slurry, and the seed crystals are grown to a desired particle size by a carbonation reaction (hereinafter, also referred to as the "seed crystal method").

[0050] In the seed crystal method, the amount of seed crystals to be mixed is preferably 1 part by mass or more and 30 parts by mass or less, more preferably 5 parts by mass or more and 20 parts by mass or less, and even more preferably 8 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of slaked lime (calculated as CaO).

[0051] In the seed crystal method, the concentration of carbon dioxide gas varies depending on the type of exhaust gas generated from each combustion engine, but when carbonation efficiency is taken into consideration, it is preferably 1 volume % or more, more preferably 5 volume % or more, and even more preferably 10 volume % or more. When carbonation efficiency and production capacity are taken into consideration, the flow rate of carbon dioxide gas is preferably 10 L / min to 200 L / min per 10 kg of the charged raw material CaO, more preferably 30 L / min to 150 L / min, and even more preferably 60 L / min to 120 L / min.

[0052] In the seed crystal method, the carbonation temperature (the temperature of the slaked lime slurry) is preferably 40°C or more and 100°C or less, more preferably 50°C or more and 90°C or less, and even more preferably 60°C or more and 80°C or less.

[0053] In the seed crystal method, it is preferable to proceed with carbonation in the presence of a phosphate. The phosphate is not particularly limited, but examples thereof include phosphoric acid, sodium dihydrogen phosphate anhydrous, sodium dihydrogen phosphate monohydrate, sodium dihydrogen phosphate dihydrate, disodium hydrogen phosphate dodecahydrate, potassium dihydrogen phosphate anhydrous, and ammonium dihydrogen phosphate anhydrous.

[0054] In the seed crystal method, the amount of phosphate to be added is preferably 1 part by mass or more and 25 parts by mass or less, more preferably 4 parts by mass or more and 18 parts by mass or less, and even more preferably 6 parts by mass or more and 12 parts by mass or less, per 100 parts by mass of slaked lime (calculated as CaO).

[0055] When a high aspect ratio is not required, a calcium carbonate compound can be produced without adding seed crystals or phosphate.

[0056] By the above procedure, a calcium carbonate compound in the form of a dispersion can be produced. In addition, a water-containing composition can be obtained by using the dispersion in which the calcium carbonate compound is dispersed as a slurry or cake without drying.

[0057] The moisture content of the obtained hydrous composition may be adjusted by adding water to the hydrous composition, by filtering or pressing the hydrous composition to remove water, or by a combination of these.

[0058] In addition to the carbon dioxide gas method, a waste seawater utilization method in which an alkaline agent such as magnesium hydroxide is added to waste seawater (residue after removing magnesium) generated when magnesium hydroxide is produced by adding slaked lime or the like to seawater, and carbon dioxide gas is blown into the waste seawater is also preferable from the viewpoint of waste utilization and carbon dioxide reduction. Furthermore, as described above, in the process of producing magnesium hydroxide from seawater, calcium carbonate compounds by-produced in the process of removing carbonates in the seawater and seawater residue mainly composed of magnesium hydroxide can also be used as the calcium carbonate compound source. The water-containing compositions obtained by these methods may be washed with water or the water content may be adjusted as described above.

[0059] <Uses of calcium carbonate compounds and water-containing compositions> The use of the calcium carbonate compound and the water-containing composition is not particularly limited. For example, the calcium carbonate compound and the water-containing composition are suitable as functional agents for inorganic molded bodies, such as building materials, and fillers for resins. Hereinafter, the embodiment in which the calcium carbonate compound and the water-containing composition are used for an inorganic molded body will be described.

[0060] The inorganic molded body is preferably formed from an inorganic composition containing a hydraulic material, a siliceous material, a reinforcing fiber material, and a calcium carbonate compound.

[0061] (hydraulic material) Examples of hydraulic materials include cementitious materials, gypsum, lime, slag, etc. Examples of cementitious materials include commonly used cements, such as ordinary Portland cement, high-early-strength cement, moderate-heat cement, fly ash cement, blast furnace slag cement, and alumina cement. Examples of gypsum include anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, etc. Examples of slag include blast furnace slag, converter slag, etc. These hydraulic materials can be used alone or in combination of two or more.

[0062] The content of the hydraulic material is preferably 5% by mass or more and 45% by mass or less, more preferably 8% by mass or more and 42% by mass or less, and even more preferably 10% by mass or more and 40% by mass or less, based on the total amount of materials constituting the inorganic molded body. By setting the content of the hydraulic material within the above range, it is possible to improve the physical properties such as bending strength and peel strength of the inorganic molded body, and to suppress the increase in bulk specific gravity of the inorganic molded body, thereby improving workability during construction.

[0063] (siliceous material) Examples of siliceous materials include materials containing a large amount of SiO2, such as silica sand, silica powder, silica fume, fly ash, diatomaceous earth, layered silicates (e.g., mica, talc, kaolin, bentonite), perlite, wollastonite, and lightweight aggregates (e.g., fly ash balloons, perlite, shirasu balloons, glass foams, etc.). These siliceous materials can be used alone or in combination of two or more. Talc, mica, and wollastonite can also be used as reinforcing fiber materials, which will be described later.

[0064] The content of the siliceous material is preferably 10% by mass or more and 55% by mass or less, more preferably 12% by mass or more and 50% by mass or less, and even more preferably 15% by mass or more and 45% by mass or less, based on the total amount of materials constituting the inorganic molded body. If the content of the siliceous material is within the above range, it becomes possible to set the bending strength, bulk density, water absorption rate, dimensional stability, etc. of the inorganic molded body within the desired range. In addition, as the siliceous material, perlite, fly ash balloons, shirasu balloons, etc., having a unit volume mass of 0.5 g / cm are preferable. 3 When mixing the following lightweight aggregates, in order to prevent the bulk density from becoming too light, which would weaken strength such as bending strength and peel strength, it is preferable to use other siliceous materials in combination so that the content of lightweight aggregate is 20 mass% or less, based on the total amount of materials constituting the inorganic molded body.

[0065] (Reinforcing fiber materials) Examples of reinforcing fiber materials that can be used include pulps such as softwood pulp, hardwood pulp, pulps fibrillated with these pulps, and pulp made by defibrating waste paper, organic reinforcing fiber materials such as vinylon fiber, acrylonitrile fiber, and polypropylene fiber, and inorganic reinforcing fiber materials such as rock wool and glass fiber. These reinforcing fiber materials can be used alone or in combination of two or more.

[0066] In order to improve the strength and toughness of the inorganic molded body, the content of the reinforcing fiber material is preferably 2% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 26% by mass or less, and even more preferably 4% by mass or more and 22% by mass or less, based on the total amount of materials constituting the inorganic molded body. By setting the content of the reinforcing fiber material within the above range, it is possible to suppress the fibers from protruding from the surface of the inorganic molded body while exerting a sufficient reinforcing effect, thereby improving the smoothness. When an inorganic reinforcing fiber material with an average length of 1 mm to 50 mm is blended as the reinforcing fiber material, it is preferable to use another reinforcing fiber material in combination so that the content is 10% by mass or less, based on the total amount of materials constituting the inorganic molded body, in order to improve the smoothness of the inorganic molded body.

[0067] (Calcium carbonate compounds) As the calcium carbonate compound, the above-mentioned calcium carbonate compound that has not been dried can be suitably used. In other words, it is preferable to use the calcium carbonate compound in the form of a water-containing composition that has not been dried for the production of an inorganic molded body.

[0068] The content (solid content) of the calcium carbonate compound is preferably 5% by mass to 60% by mass, more preferably 8% by mass to 55% by mass, and even more preferably 12% by mass to 50% by mass, based on the total amount of materials constituting the inorganic molded body. By blending a calcium carbonate compound with low thermal conductivity in the above range, the heat insulation in the thickness direction of the inorganic molded body is improved, and the rise in the back surface temperature can be suppressed to a high level.

[0069] (optional ingredient) In addition to the above materials, in order to impart various functions to the inorganic molded body, various materials such as resin hollow bodies, wood chips, wood powder, resin powder, defoamers, flocculants, water repellents, thickeners (methyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, etc.), dispersants, etc. can be mixed into the inorganic molded body depending on the purpose. It is also possible to appropriately add recycled materials obtained by crushing scraps generated during processing of the inorganic molded body.

[0070] (Method for producing inorganic molded body) The method for producing the inorganic molded body according to the present embodiment is not particularly limited, and includes a step of molding an inorganic composition containing the water-containing composition. As the molding method, a papermaking method, an extrusion molding method, a flow-on molding method, a casting molding method, a press (compression) molding method, etc., which are commonly used, can be used. The inorganic molded body can be obtained by subjecting a green sheet molded by these methods to a dehydration step such as press dehydration and / or a patterning processing step such as embossing, and then through a curing step such as room temperature curing, steam curing, autoclave curing, etc. Furthermore, a drying step is performed, and a shaping step or a painting step may be performed as necessary.

[0071] (Uses of inorganic molded bodies) The use of the inorganic molded body is not particularly limited, and it can be suitably used as a performance maintaining material such as a wall material, a floor material, a roofing material, various boards, external decorative members, interior and exterior finishing materials such as fittings, a sealing material, a heat insulating material, a sound absorbing material, a waterproofing material, etc. The inorganic molded body is preferably a cement-based molded body containing a cementitious material, and more preferably a calcium silicate molded body. Among them, the molded body is more preferably a molded board. EXAMPLES

[0072] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. Measurements and evaluations of physical properties, etc. were performed as follows.

[0073] <Evaluation of calcium carbonate compounds> The following analyses were carried out on the water-containing compositions and calcium carbonate compounds obtained in the Examples and Comparative Examples. The results of each analysis are shown in Table 1 and Figures 1 and 2. In Table 1, the arrows indicate that the results were the same as those in the left column.

[0074] (1) BET specific surface area The sample powder was pretreated in a nitrogen gas atmosphere at approximately 130°C for approximately 30 minutes using an 8-unit preheat unit (MOUNTECH), and the BET specific surface area (m2) was measured by nitrogen gas adsorption using a Macsorb HM Model-1208 (MOUNTECH) BET specific surface area measuring device. 2 / g) was measured. Note that in order to measure the BET specific surface area, it is necessary to measure it on a dried powdered sample. Therefore, in the case of a sample cake or sample slurry, the sample powder for BET specific surface area measurement was prepared by drying the sample cake or sample slurry at 110°C for 24 hours.

[0075] (2) Average particle size by laser diffraction method 50 mL of ethanol was placed in a 100 mL beaker, and about 0.3 g of sample cake, about 0.6 mL of sample slurry, and about 0.2 g of sample powder were placed in the 100 mL beaker, and ultrasonic treatment (Tomy Seiko UD-201) was performed for 3 minutes to prepare a dispersion. The volumetric D of this dispersion was measured using a laser diffraction particle size distribution analyzer (Nikkiso Microtrac HRA Model 9320-X100). 50 The value was measured as the average particle size (μm).

[0076] (3) Calculation of average major axis, average minor axis and aspect ratio by scanning electron microscope observation Double-sided tape was attached on an aluminum sample stage, and the sample powder was applied on the tape by tracing it with a spatula. After platinum deposition, the particle image of the sample powder was photographed at 2,000 times magnification using a scanning electron microscope (FE-SEM: S-4700 manufactured by Hitachi, Ltd.). SEM photographs are shown in Figures 1 and 2. Figure 1 is an SEM photograph of a calcium carbonate compound obtained from the water-containing composition of Example 1-1. Figure 2 is an SEM photograph of a calcium carbonate compound obtained from the water-containing composition of Example 1-2. For the obtained SEM photograph, 20 particles in the photograph were randomly selected using image analysis software (Image J), ​​and the average values ​​of the major axis, minor axis, and aspect ratio (ratio of major axis to minor axis) of the primary particles were calculated. Note that in order to observe with a scanning electron microscope, it is necessary to observe the sample in a dried powder form. Therefore, in the case of a sample cake or a sample slurry, these were dried at 110 ° C for 24 hours to prepare a sample powder for scanning electron microscope observation.

[0077] (4) 46° (aragonite) peak intensity I by XRD measurement a 29° (calcite) peak intensity I c Calculating the ratio to The sample powder was pressed and fixed on a specified sample stage with a spatula, and then measured using an XRD device (MiniFlex600-C, manufactured by Rigaku Corporation) to perform identification analysis as a crystalline substance. Note that, at the measurement angle 2θ, the peak appearing at approximately 29° is the main peak of calcite, and the peak appearing at approximately 46° is the main peak of aragonite. From this, the 46° (aragonite) peak intensity I a 29° (calcite) peak intensity I c Ratio to (I a / I c ) was obtained. In order to measure XRD, it is necessary to measure the sample in a dried powder form. Therefore, in the case of sample cakes or sample slurries, these were dried at 110°C for 24 hours to prepare sample powder for XRD measurement.

[0078] (5) Dynamic viscosity, static viscosity and thixotropy The dynamic viscosity, static viscosity and thixotropy value of the slurry prepared to a predetermined concentration were measured. That is, the viscosity (dynamic viscosity) at a rotor rotation speed of 30 rpm and the viscosity (static viscosity) at 6 rpm were measured using a B-type viscometer. The thixotropy value was calculated by subtracting the viscosity μ6 at 6 rpm from the viscosity μ6 at 30 rpm. 30 The value obtained by dividing by (μ6 / μ 30 ) was calculated.

[0079] <Production of Water-Containing Composition Containing Calcium Carbonate Compound> [Example 1-1] Calcium carbonate compound (aspect ratio 10.4) 6980g of slaked lime powder (calculated as CaO), 630g of aragonite seed crystal powder, and 500g of disodium hydrogen phosphate dodecahydrate were prepared and charged into a 220L SUS vessel with a baffle plate, which was filled with 180L of water, under stirring to prepare a mixed slurry of the raw materials. The mixture was then heated to 70°C and stirred at 150rpm using a stirrer equipped with one turbine blade at that temperature. A pipe for extracting exhaust gas was connected to the exhaust outlet of a steam production boiler that uses LNG as fuel, and the CO2 concentration was measured using a CO2 concentration meter (XP-3140 manufactured by Shin Cosmos Electric Co., Ltd.) while drawing in the exhaust gas using a test blower. The CO2 concentration was 10% by volume. Exhaust gas was introduced into the 220L SUS vessel described above using a test blower at a speed of 100L / min, and a carbonation reaction was carried out for 7 hours. After that, it was filtered with a test filter press and washed with about 5 times the amount of water relative to the solid content to obtain a sample cake with a CaCO3 concentration of 75% by mass. For the evaluation of calcium carbonate, a part of the sample cake was taken out and used as it was without drying. In addition, the sample cake was emulsified in water to prepare a sample slurry of calcium carbonate with a CaCO3 concentration of 33% by mass.

[0080] [Example 1-2] Calcium carbonate compound (aspect ratio 2.7) A sample cake and a sample slurry of calcium carbonate compounds were obtained by carrying out the same procedure as in Example 1-1, except that 7,170 g of milk of lime (calculated as CaO) was prepared, no aragonite seed crystals or disodium hydrogen phosphate dodecahydrate was added, and the reaction temperature was set to 40°C.

[0081] [Comparative Example 1-1] Calcium carbonate compound (aspect ratio 10.4) The same operations as in Example 1-1 were carried out up to the carbonation reaction. Then, the mixture was filtered with a test filter press, washed, dried at 110° C. for 24 hours, and pulverized to obtain a calcium carbonate powder sample.

[0082] [Comparative Example 1-2] Calcium carbonate compound (aspect ratio 2.7) The same operations as in Example 1-2 were carried out up to the carbonation reaction. Then, the mixture was filtered with a test filter press, washed, dried at 110°C for 24 hours, and pulverized to obtain a calcium carbonate powder sample.

[0083] [Table 1]

[0084] <Production of Inorganic Molded Body> Inorganic molded bodies were manufactured by the papermaking method and extrusion molding method according to the following procedures. The amounts of the components used are all shown in "parts by mass" unless otherwise specified. In the table below, "-" indicates that the corresponding component was not used.

[0085] [Production Example 1-1] Production of inorganic molded body by papermaking method The materials shown in Table 2 below were put into a plastic container and mixed by stirring to obtain a raw material slurry. As a calcium carbonate compound, the sample slurry of Example 1-1 (CaCO3 concentration 33 mass%) was used so as to obtain the amount of calcium carbonate compound shown in Table 2. The raw material slurry was divided and put into a filter covered with felt, and a laminated board (long side 28 mm x short side 24 mm x thickness 14 mm) was produced while performing suction filtration with a vacuum pump. The laminated board was removed from the filter and subjected to dehydration pressing. The thickness after pressing was 13 mm. After autoclave curing (curing pressure (gauge pressure) 9 kgf; curing time 12 hr), the pressed body was dried in a dryer (105 ° C) for 24 hr. Both sides were polished with a sander to adjust the thickness to 12 mm, and an inorganic molded body was obtained.

[0086] [Production Example 1-2] Production of inorganic molded body by papermaking method An inorganic formed body was obtained in the same manner as in Production Example 1-1, except that the sample slurry of Example 1-2 (CaCO3 concentration: 33 mass %) was used as the calcium carbonate compound.

[0087] [Comparative Manufacturing Example 1-1] Manufacturing of inorganic molded body by papermaking method An inorganic formed body was obtained in the same manner as in Production Example 1-1, except that the sample powder of Comparative Example 1-1 was used as the calcium carbonate compound.

[0088] [Comparative Manufacturing Example 1-2] Manufacturing of inorganic molded body by papermaking method An inorganic formed body was obtained in the same manner as in Production Example 1-1, except that the sample powder of Comparative Example 1-2 was used as the calcium carbonate compound.

[0089] <Evaluation of inorganic molded bodies> The inorganic molded bodies produced by the papermaking method in the Production Examples and Comparative Production Examples were evaluated as follows. The results are shown in Tables 2 and 3.

[0090] (bulk density) The bulk density was measured in accordance with JIS A 5430.

[0091] (Heating test) The heating test was carried out with the following equipment and procedure. Figure 5 is a partial perspective view that shows a schematic diagram of the heating tester. As shown in Figure 5, an electric heater was used as the heat source, and fireproof material was installed between the test specimen and the heat source so that the temperature could be stabilized at around 900°C, and the temperature of the back side of the test specimen could be measured with a thermocouple. Specifically, an electric heater (1.2 kW heater) was used as the heat source equipment, and a K thermocouple and a temperature regulator were connected. In addition, each thermocouple was connected to a data logger. The distance between the heating surface of the test specimen and the heat source was fixed at approximately 70 mm.

[0092] The test procedure was as follows. (1) A scrap board was placed and preheating was performed up to 902°C, after which heating was performed once. (2) The test specimen was inserted after the heated surface had cooled below 200°C. (3) A thermocouple was placed in the center of the back surface of the test specimen (top surface in the figure), and a calcium silicate plate (approximately 30 mm x 70 mm) and a weight were placed on top and fixed in place. (4) Heating was started, and the specimen was left for a specified time (45 minutes), after which the temperatures of the front and back sides were recorded with a data logger. During this time, the temperature of the electric heater was set to 902°C on the heating side, and was controlled with a temperature controller with a lower limit of 900°C. The data logger also measured the temperature every 10 seconds, and the data was recorded at this interval. (5) After the test was completed, the test specimens were removed and the following items were measured (each item was also measured before the test): Dimensions: The length and width of the back surface and the heated surface were measured with a caliper. The area of ​​the heated surface (mm 2 ) was calculated, and the heating surface shrinkage (%) was calculated based on the following formula: Heating surface shrinkage (%) = {|S1-S0| / S0} x 100 (In the formula, S0 is the area of ​​the heated surface before the test, and S1 is the area of ​​the heated surface after the test.)

[0093] [Table 2]

[0094] The inorganic molded body of the manufacturing example was superior to the comparative manufacturing example in both the heated surface shrinkage and the back surface temperature rise. In addition, the inorganic molded body of the manufacturing example had a strength sufficient for practical use, and did not develop cracks after heating (not shown).

[0095] [Production Example 2-1] Production of inorganic molded body by extrusion molding method The materials shown in Table 3 below were put into an Omnimixer and the raw materials were dry-mixed for 3 minutes. As a calcium carbonate compound, the sample cake of Example 1-1 (CaCO3 concentration 75% by mass) was used so as to obtain the amount of calcium carbonate compound shown in Table 2. Next, water was added and wet-mixed for 2 minutes. The raw materials after wet mixing were kneaded with an Ishikawa-ji extruder, and then extrusion-molded with the Ishikawa-ji extruder. This produced a molded body (long side 600 mm x short side 190 mm x thickness 13 mm). After obtaining the molded body, it was put into a thermostatic chamber set at 60°C / 98% and subjected to primary curing, and further pressure was increased to 9 kgf and autoclave curing was performed for 12 hours. Both sides of the molded body were polished with a sander to make the thickness 12 mm, producing an inorganic molded body.

[0096] [Production Example 2-2] Production of inorganic molded body by extrusion molding method An inorganic formed body was obtained in the same manner as in Production Example 2-1, except that the sample cake of Example 1-2 (CaCO3 concentration: 75 mass %) was used as the calcium carbonate compound.

[0097] [Comparative Production Example 2-1] Production of inorganic molded body by extrusion molding method An inorganic formed body was obtained in the same manner as in Production Example 2-1, except that the sample powder of Comparative Example 1-1 was used as the calcium carbonate compound.

[0098] [Comparative Manufacturing Example 2-2] Manufacturing of inorganic molded body by extrusion molding method An inorganic formed body was obtained in the same manner as in Production Example 2-1, except that the sample powder of Comparative Example 1-2 was used as the calcium carbonate compound.

[0099] <Evaluation of inorganic molded bodies> The inorganic molded bodies produced by extrusion molding in the Production Examples and Comparative Production Examples were evaluated as follows. The results are shown in Table 3.

[0100] (bulk density) The bulk density was measured in accordance with JIS A 5430.

[0101] (Heating test) The measurement was carried out in the same manner as in the papermaking method.

[0102] [Table 3]

[0103] The inorganic molded body of the manufacturing example was superior to the comparative manufacturing example in both the heating surface shrinkage and the warpage after heating. Moreover, the inorganic molded body of the manufacturing example had a strength sufficient for practical use, and did not develop cracks after heating (not shown).

Claims

1. A calcium carbonate compound having a viscosity of 1000 cP or more and 2000 cP or less at 30 rpm when dispersed in water at a concentration of 33% by mass.

2. 2. The calcium carbonate compound according to claim 1, wherein the viscosity of a dispersion of the compound dispersed in water at a concentration of 33% by mass at 6 rpm is 1000 cP or more and 2500 cP or less.

3. Viscosity μ of the dispersion at 6 rpm when dispersed in water at a concentration of 33% by mass 6 Viscosity μ at 30 rpm 30 Ratio to μ 6 / μ 30 The calcium carbonate compound according to claim 2, wherein the calcium carbonate content is 1.0 or more and 2.5 or less.

4. 2. The calcium carbonate compound according to claim 1, having an aspect ratio of the average major axis to the average minor axis of 2 or more and 19 or less.

5. 2. The calcium carbonate compound according to claim 1, having an average particle size of 1.1 μm or more and 12.5 μm or less as measured by a laser diffraction method.

6. 2. The calcium carbonate compound according to claim 1, having an average major axis of 0.5 μm or more and 25 μm or less as measured by scanning electron microscopy.

7. A water-containing composition comprising water and the calcium carbonate compound according to any one of claims 1 to 6.

8. The water-containing composition according to claim 7, having a water content of 40% by mass or more and 99% by mass or less.

9. The water-containing composition according to claim 7, having a water content of 5% by mass or more and 60% by mass or less.

10. The water-containing composition according to claim 7, which is obtained without drying in the production process of the synthetic calcium carbonate compound.

11. An inorganic formed body comprising the calcium carbonate compound according to any one of claims 1 to 6.

12. A method for producing an inorganic molded body, comprising a step of molding an inorganic composition containing the water-containing composition according to any one of claims 7 to 10.

Citation Information

Patent Citations

  • Calcium carbonate wet grinding dispersing agent

    CN101322928A

  • Manufacture of 0*1*1*0 micron calcium carbonate

    JP1981017924A

  • Preparation of calcium carbonate dispersion

    JP1993319815A

  • Production of spherical or spheroidal vaterite calcium carbonate

    JP1999314915A

  • Method of producing calcium carbonate slurry with calcium carbonate aggregated particle dispersed

    JP2003119021A